Penatalaksanaan Fisioterapi Pada Kasus Cervical Root Syndrome Dengan Modalitas Tens Dan Terapi Latihan Di Rsud Saras Husada Purworejo - Dewi, Isnaini Kusuma; , Totok Budi Santoso, S.Fis., SPd., MPH (2015)
Background: Cervical Root Syndrome is a collection of symptoms that are very disturbing patients usually bigger activity caused by muscle work habits at the wrong moment can also be caused by age (degenerative) of joint disease. so that appropriate treatment can be given usually in the form of non opratif handling very heavy and if the complaint can be done surgically to improved patient's condition. Symptoms such as neck pain that spreads to the shoulders, upper arms and lower, parasthesis and weakness or muscle spasm. Pain that arises often they are due oeleh the injury at or near the root of the nerve spina. Objective: To determine the management of transcutaneous electrical nerve stimulation (TENS) can reduce pain in conditions Root Cervical Syndrome and to determine containment procedures Exercise therapy can increase the area of motion and spasm of the neck on condition Root Cervical Syndrome. Results: Reduction of motion pain becomes Lt = 6.5 T6 = 2.7 and tenderness T1 = 5 to T6 = 2.7 Increased LGS flexi T1 = 6 cm into T6 = 9.5 cm, the extension T1 = 4cm into T6 = 5cm, lateral right flexsi T1 = 7cm be T6 = 9 cm, lateral left flexi T1 = 6 cm into T6 = 7 cm, right rotation T1 = 11cm into T6 = 11,5cm, left rotation T1 = 6 cm to T6 = 10 cm and decrease in spasm spasm ie T1 = still exist, T2 = still exist, T3 = reduced, T4 = reduced, T5 and T6 = there = no. Methods: A case study in which patients studied and observed progress during therapy six times. Conclusion: Various problems that arise on condition of cervical root of this syndrome are pain, limitation of LGS (range of motion) and spasm. Physiotherapy modalities are used to address the problem that TENS and exercise therapy. In addition patients were given education to do the exercises at home as it has been taught by the therapist. With the implementation modalities of therapy using the results obtained show a positive development which is evidenced by the decrease in pain (tenderness and pain motion) increase in LGS (range of motion), drop in spasm.